Risk Factors Influencing the Degree of Tuberculous Spondylitis Based on MRI Modality - Sadewo, Mukti; Sukmaningtyas, Hermina; Priambodo, Agus; Prihharsanti, Christina Hari Nawangsih (Indonesian Journal of Tropical and Infectious Disease, 2023)
The high prevalence and mortality of tuberculosis (TB) is serious threats to the world. Tuberculous spondylitis accounts for 50% of all bone and joint TB cases. The accuracy of diagnosis to detect disease severity using Magnetic Resonance Imaging (MRI) modalities is important when considering potential risk factors. This study aimed to analyze the association of risk factors, including age, sex, spinal lesion location, and abscess location, with the severity of tuberculous spondylitis based on MRI modality using the Gulhane Askari Tip Akademisi (GATA) classification. This study had a cross-sectional design. The study sample consisted of 50 patients who met the inclusion criteria and underwent MRI. The statistical analysis performed in this study was multivariate analysis using multiple linear regression. The results showed that 84% (n = 42) of tuberculous spondylitis affected patients aged 18-65 years, and 70% (n = 35) of cases were found in female patients. In addition, 42% (n = 21) of cases were classified as tuberculous spondylitis grade III according to the GATA classification and were the most common cases in this study. Statistical tests showed no association between age, the location of spinal lesions, and the degree of tuberculous spondylitis. However, there was an association between sex, spinal abscess location, and degree of tuberculous spondylitis. There was no significant association between age and spinal lesion location or degree of tuberculous spondylitis. However, there was a significant association between sex, spinal abscess location, and the degree of tuberculous spondylitis.